Fractional order epidemiological model of SARS-CoV-2 dynamism involving Alzheimer’s disease - Addai, Emmanuel; Zhang, Lingling; Preko, Ama Kyerewaa; Asamoah, Joshua Kiddy K. (Elsevier, 2024)
This article is published by Elsevier 2022 and is also available at www.elsevier.com/locate/health